Pengaruh Profesional Identity pada Turnover Intention dengan Employee Enggagement dan Job Satisfaction sebagai Variabel Mediasi - Missye, Missye; Hosen, Chandra (Universitas Bunda Mulia, 2024)
The high level of employee turnover intention is an important problem for companies. Companies to make efforts to increase job satisfaction and employee engagement in their work, so that it will have an impact on reducing turnover intentions. Research was conducted on employees to analyze the influence of professional identity on turnover intention with employee engagement and job satisfaction as mediation. This research uses a quantitative approach using a questionnaire filled out by 42 respondents who work at company.. techniques probability sampling with simple random sampling. The results show that professional identity, job satisfaction and work engagement have a negative influence on turnover intention. Meanwhile, professional identity has a positive effect on employee engagement and job satisfaction. Job satisfaction and employee engagement are able to mediate the influence of professional identity on turnover intention. In an effort to minimize employees turnover intention , companies need to improve their professional identity, which can have an impact on employee engagement and employee job satisfaction which will have the effect of lowering turnover intention.